Reference rates for cohort studies in Italy: an essential tool in occupational and residential cohort studies - Pirastu, Roberta; Ranucci, Alessandra; Consonni, Dario; De Santis, Marco; Bruno, Caterina; Conti, Susanna; Fazzo, Lucia; Iavarone, Ivano; Pasetto, Roberto; Zona, Amerigo; Magnani, Corrado; Comba, Pietro (La Medicina del Lavoro, 2016)
The cohort study aims to test the hypothesis of an association between specific exposure/s and adverse health outcomes. The cohorts include the subjects who experience the exposure/s and are followed up over time to ascertain the health outcomes. This contribution presents the database for the analysis of mortality studies which is made available for public institutions carrying out cohort studies in Italy. The rates were computed from official mortality data from ISTAT. The database contains 141 causes or groups of causes for the years 1970-2012 ensuring correspondence with subsequent editions of ICD (International Classification of Diseases) VIII, IX and X.